2006
DOI: 10.1303/aez.2006.1
|View full text |Cite
|
Sign up to set email alerts
|

Key themes in the study of seasonal adaptations in insects II. Life-cycle patterns

Abstract: Recent work on selected topics of particular interest for understanding insect life-cycles is reviewed, including habitat patterns, kinds of variation, the spreading of risk and prolonged diapause, trade-offs and developmental plasticity, circannual rhythms, the concept of life cycles as developmental choices, and development or delay as the default response. Seasonal adaptations have a wider range of components than has often been appreciated. Variation in lifecycle traits, including the duration of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 134 publications
2
71
0
2
Order By: Relevance
“…Thirdly, Lowe et al (2009) found, in the most exhaustive study to date, that egg laying was strongly right-skewed in C. puella. This right-skewness is likely a general pattern in summer-active species, as it has been observed previously in diverse taxa, including plants, insects, and birds (Rabinowitz et al 1981, Danks 2006, Laaksonen et al 2006.…”
Section: Modeling Hatching Datessupporting
confidence: 76%
“…Thirdly, Lowe et al (2009) found, in the most exhaustive study to date, that egg laying was strongly right-skewed in C. puella. This right-skewness is likely a general pattern in summer-active species, as it has been observed previously in diverse taxa, including plants, insects, and birds (Rabinowitz et al 1981, Danks 2006, Laaksonen et al 2006.…”
Section: Modeling Hatching Datessupporting
confidence: 76%
“…In some cases the rhythmic activity is stimulated or elicited exogenously by an acute rhythmic environmental factor, such as when a threshold level of light, temperature, moisture, or mechanical disturbance is reached (Lockwood & Story 1985;Tomioka et al 1991;Danks 2005;Bradshaw & Holzapfel 2010). In other cases, the timing of the activity is determined endogenously by an internal biological clock, which itself was previously set by a zeitgeber (an external oscillating environmental factor that entrains a biological rhythm) (Bünning 1967;Danks 2006;Koštál 2011;Saunders & Bertossa 2011). Often, both exogenous and endogenous processes work together to determine the specific pattern; i.e., acute, current environmental stimuli alter the expression of existing circadian rhythms (Lockwood & Story 1985;Tomioka et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Insects have evolved numerous life history strategies, which have enabled them to adapt their ontogeny and reproduction to seasonal changes in their environment (Masaki, 1996;Tauber et al, 1986;Musolin & Saulich, 1999;Danks, 2002Danks, , 2006a. In terms of population development, the diversity in life history traits divides insect species into two categories (Danks, 2001): First, those with only one generation (univoltinism) and second those with several generations per year (multivoltinism).…”
Section: Introductionmentioning
confidence: 99%